2013
DOI: 10.1080/19393210.2013.767862
|View full text |Cite
|
Sign up to set email alerts
|

Fusariotoxins in Russian Federation 2005–2010 grain harvests

Abstract: Monitoring results of food grain contamination with fusariotoxins-deoxynivalenol (DON), zearalenone (ZEN), fumonisins (FB1&FB2), T-2 and HT-2 toxins-are presented. Harvests of 2005-2010 in different regions of Russia were investigated. The occurrence of DON in wheat was 8%, barley 9%, oats 4%, rye 2% and maize 2%. The highest frequency of ZEN contamination was found in oats, the lowest in wheat. Calculated average daily intake of DON varied from 0.066 to 0.096 µg/kg body weight, the highest being found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
1
11
1
4
Order By: Relevance
“…A Russian group monitored Fusarium toxins in wheat, barley, oats, rye, and maize between 2005 and 2010. Their results demonstrated the presence of T-2 toxin in 14% and HT-2 toxin in 17% of all samples (17). Our results showed that contamination of T-2 and HT-2 in crops also occurred in the pan-Pacific zone, including Japan, Canada, and the United States.…”
Section: Occurrence Of Don Zen T-2 and Ht-2 In Wheatmentioning
confidence: 44%
See 1 more Smart Citation
“…A Russian group monitored Fusarium toxins in wheat, barley, oats, rye, and maize between 2005 and 2010. Their results demonstrated the presence of T-2 toxin in 14% and HT-2 toxin in 17% of all samples (17). Our results showed that contamination of T-2 and HT-2 in crops also occurred in the pan-Pacific zone, including Japan, Canada, and the United States.…”
Section: Occurrence Of Don Zen T-2 and Ht-2 In Wheatmentioning
confidence: 44%
“…The natural occurrence of these mycotoxins is frequent in a wide variety of agricultural products, such as com, wheat, and barley, and is of great concern to animal and human health (11,12,17,18). Trichothecenes can be divided into type A and type B depending on their structures.…”
mentioning
confidence: 99%
“…In Lithuania, Mankevičienė et al [ 18 ] found that 50% of rye samples were contaminated by DON, with a maximum concentration of 158.9 µg/kg. In one out of 63 rye samples (2%), DON was found at a concentration of 60 µg/kg in a 6-year survey in the Russian Federation [ 19 ]. In another study, Remža et al [ 20 ] analyzed 39 Slovak rye grains, and DON was found at mean and maximum concentrations of 67.9 µg/kg and 289.0 µg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(Streit et al, ). Although the contamination level of T‐2 toxin is relatively lower than DON worldwide, it is still very common in many areas (Bhat & Reddy, ; EFSA, ; Pascale et al, ; Pinotti et al, ; Tutelyan et al, ; Yoshinari et al, ). T‐2 toxin is also a non‐negligible highly toxic mycotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…In a large‐scale study between 2005 and 2010, T‐2 toxin was present in 23% of the food, feed and unprocessed grains collected from 22 European countries (EFSA, ). The Russian Federation monitoring the presence of Fusarium toxins reported that T‐2 toxin was found in 14% of grain samples harvested in 2005–10 (Tutelyan et al, ). In a Japanese survey between 2010 and 2012, T‐2 toxin was detected in 10% of wheat flour, 20% of corn grits, 22% of Job's tears products, 57% of beers and 70% of adzuki beans (Yoshinari et al, ).…”
Section: Introductionmentioning
confidence: 99%